Convergence of composition sequences of bilinear and other transformations {fn},fn→z - John Gill (International Journal of Mathematics and Mathematical Sciences)
This paper investigates convergence behavior of composition sequences f1∘f2∘…∘fn(z) and fn∘fn−1∘…∘f1(z) where the fn's are bilinear transformations and fn→z. Additional results are provided for the case when the fn's are more general functions.